Dampak Menonton Anime terhadap Tingkat Motivasi Siswa SMP - Muhamad Rizqi Seputro; Desy Safitri; Sujarwo (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2025)
The phenomenon of escalating anime consumption as a form of entertainment among junior high school students (Sekolah Menengah Pertama, SMP) generates an imperative to comprehend its psychological and educational ramifications, particularly concerning learning motivation. This study employs a systematic literature review methodology to analyze the correlation between anime exposure and the learning motivation levels of SMP students, with a particular focus on both intrinsic and extrinsic motivational dimensions. The synthesized literature reveals that anime, through its narrative complexity, visual quality, and motivational character portrayal, functions as a stimulus capable of enhancing intrinsic motivation by instilling ethical values and achievement-oriented zeal, as well as facilitating extrinsic motivation via social recognition incentives and identity aspirations. This augmentation in motivation contributes positively to increased concentration, active participation, and learning perseverance. Nonetheless, findings also indicate potential risks of diminished learning efficacy attributable to disproportionate time allocation towards excessive anime viewing, which may adversely impact academic performance. The contribution of this research lies in the integration of motivational theory (intrinsic and extrinsic) with media effects theory within the context of anime genres—particularly the action genre—to explicate the dynamics of media influence on cognitive, affective, and behavioral learning facets. Overall, the study concludes that the influence of anime consumption on junior high school students’ learning motivation is dualistic in nature; anime can serve as a facilitative medium for learning motivation when consumed in a controlled manner. Therefore, time management and content comprehension emerge as critical factors in optimizing the educational benefits of anime consumption without eliciting detrimental consequences on academic achievement.